Magnitude of Retranslocation of N, P, K in Eucalyptus Hybrid Intercropped with Aromatic Crop - Morsin, Faiz; Singh, K.; Singh, R. P. (Indian Forester, 1999)
The annual litter production increased with increasing age of the Eucalyptus plantations both in the pure and intercropped stands with Mentha and Cymbopogon spp. An increase in litter production was recorded in all the intercropped in comparison to pure stands at all the ages. Higher concentration ofN, P and K was observed in the litter of the intercropped stands which decreased with increasing ages of the stands. Nutrient concentration in green foliage, decreased with increasing ages of the stands. It was higher in the stands intercropped with Mentha and Cymbopogon spp. Than the pure stands. Magnitude of retranslocation (%) in pure as well as intercropped plantation, increased with increasing ages of the stands.